Orchestration competence in innovation ecosystem - Lisiane Machado; Kadígia Faccin; Bruno Anicet Bittencourt (Innovation & Management Review, 2025)
The paper aims to propose the definition of individual orchestration competence concept and the identification of its main attributes for orchestrating innovation ecosystems.A literature review was conducted, from 2006 to 2024, considering Dhanaraj and Parkhe (2006) as a theoretical-conceptual framework, in Scopus and Web of Science databases. Seminal articles, books, articles and references cited in the selected articles were also used.In this research, we highlight the need for competence for orchestrators to work in an innovation ecosystem. For this, we propose individual orchestration competence and its attributes. Next, we propose the Individual Orchestration Competence Theoretical Model in Innovation Ecosystem.The results advance the field of orchestration by promoting the expansion of the network and ecosystem orchestration model, from the perspective of orchestrators' roles and activities and orchestration dimension, to an ecosystemic and dynamic orchestration competence model.As theoretical contributions, the proposition of individual orchestration competence concept and its attributes. Also the expansion of the existing theoretical model to a competence approach. As managerial contributions, we highlight the orchestration competence required of innovation ecosystem orchestrators.Social implications are promoted as orchestrators understand their importance in the innovation ecosystem.The orchestration literature has focused on its roles, activities and dimensions. Recently, the different orchestrators' roles have been discussed, but little progress has been made. Therefore, this study has the novelty of exploring individual level - the orchestrator -, proposing an individual orchestration competence model.
Keywords: 650; Innovation ecosystem; Orchestration; Competence; Orchestration competence